IEEE Fellows Survey Bursting Tech Bubbles Before They Balloon. - Gorbis, M.
The Institute for the Future (IFTF) and IEEE Spectrum conducted an online survey between February and March 2006 among more than 700 IEEE Fellows from all over the globe to identify key breakthroughs in their areas of expertise and to forecast probabilities of specific developments. Called The Future of Science and Technology Survey, it identified several forecast domains that included computer science, telecommunications and media, sensors and robotics, materials and nanotechnology, energy, physics, space and earth sciences, and human health and biology
Keywords: IEEE Spectrum; Institute for the Future; Biology; Computer science; Forecast domains; Human health; Robotics; Sensors